A Forever Kind of Love - Roberts, Nora; Roberts, Nora. (Toronto, Ontario : Silhouette Special Releases, 2021)
Waiting for Nick: Frederica Kimball has had a crush on Nicholas LeBeck since they were kids. Once a reckless teenager, Nick has cleaned up his act and is now one of the most sought-after composers on Broadway. So when Freddie is offered the opportunity to work on a musical with Nick, she wastes no time. She moves to New York City to be closer to Nick...and to be independent for once. Freddie is tired of being looked at like a helpless child and determined to prove shes not a little girl anymore. If only Nick would see things that way, too... Considering Kate: Kate Stanislaski Kimball is ready for change. After years in the spotlight, Kate retires from her job as a prima ballerina and decides to open a dance studio in her small hometown. She finally owns the historic building she admired as a kid but needs help fixing it up--which comes in the form of handsome contractor Brody OConnell. Kate is attracted to Brody the first time she sees him, though Brody insists hes not interested. But no matter how professional Brody tries to keep their relationship, theres no denying the connection he feels with Kate.
Keywords: Composers -- Fiction; Ballerinas -- Fiction; Contractors -- Fiction; Electronic books; Romance fiction